Analyze the Association Between Birth Attendant, Type Relationship Helper, Type and Problems/Disturbance of Delivery with The Level of Anemia in Mothers - Sharief, Suchi Avnalurini; Patimah, Sitti (Yayasan Ahmad Mansyur Nasirah, 2024)
In Indonesia, the causes of anemia in pregnancy are multifactorial, but in general iron deficiency is considered the main cause because anemia diagnosis is generally based on hemoglobin measurements. This research aims to analyze the relationship between helper, type, and birth problems/disruptions, and the degree of anemia in the mother. The type of research was analytical observational with a cross-sectional study design, the sampling technique was purposive sampling with a research period of October-November 2023. Of the 41 in-partum mothers with anemia at RSIA Masyita, Makassar City, there were 85.4% of the mothers with mild anemia, 14.6 % had moderate anemia, and no severe anemia was found in this study. The Chi-Square test was used to see maternal outcomes. For birth attendants with a p-value of 0.01, type of birth 0.06, birth problems/disorders 0.02. There were 16 mothers with anemia who experienced problems during delivery consisting of, 3 (18.7%) experienced hypertension, 3 (18.7%) experienced umbilical cord entanglement, 3 (18.7%) experienced prolonged labor, 5 (31.3%) experienced Premature Rupture of Membranes (PROM), 1 (6.3%) experienced serotinus and 1 (6.3%) experienced placenta previa. The conclusion is that the type of anemia influences the assistance and problems/disruptions during childbirth. Future researchers are expected to carry out monitoring not only focusing on the mother but also on the baby.